Application of a simulation algorithm to a specific liquid propellant engine with experimental verification - Karimi, Hassan; Nassirharand, Amir (Aircraft Engineering, 2006)
Purpose - The purpose of this paper is to apply a new systematic simulation approach to an existing liquid propellant engine.Design methodology approach - The simulation approach is based on following the liquids (oxidizer and fuel) in their respective paths. The nonlinear dynamic model of the engine is composed of implicit nonlinear algebraic equations coupled with a set of differential equations. The model is solved by placing the implicit nonlinear algebraic equations in a set of nested Newton-Raphson loops followed by numerical integration of the differential equations using a first-order Euler technique.Findings - It is found that the simulation algorithm may successfully be applied to an operating point model to predict the steady-state values with errors under 10 percent. These results indicate that such engine models may be used to design reiable robust engine control systems because a robust control system design would allow for about 20 percent discrepancy between the model and the actual case.Research limitations implications - At present, the research is limited to liquid propellant engines that are modeled by a set of implicit nonlinear algebraic equations coupled with a set of differential equations; engine models that are entirely modeled by differential equations are subject of future research.Practical implications - The major outcome of this research is that verifies liquid engines may be simulated by the novel idea of following the engine liquids in their respective paths.Originality value - This is the first paper that adapts an existing simulation algorithm for simulation of the specific liquid engine under study with experimental verification.